2011
DOI: 10.1021/ef201229j
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Performance of Levulinate Esters as Diesel Blend Components

Abstract: The properties of ethyl (EL) and n-butyl levulinate (BL), two potential cellulose-derived diesel blend components, were assessed as both neat oxygenates and blends with diesel fuel. The samples tested were produced commercially from cellulose and alcohols but were not reagent-grade samples. They were relatively free of impurities, although EL contained some acidic compounds and both contained parts-per-million levels of calcium. Both esters exhibited a very low cetane number. The melting points of both esters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
132
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(136 citation statements)
references
References 19 publications
3
132
1
Order By: Relevance
“…Absolute error percentage was recorded at 6.78%. According to Christensen et al, presence of butyl levulinate in fuel blend reduce cetane number of the blend [21]. However, this claim is contradicting to the finding from this study as both predicted and tested fuel blend cetane number were higher than the EN590 minimum limit.…”
Section: Resultscontrasting
confidence: 95%
See 2 more Smart Citations
“…Absolute error percentage was recorded at 6.78%. According to Christensen et al, presence of butyl levulinate in fuel blend reduce cetane number of the blend [21]. However, this claim is contradicting to the finding from this study as both predicted and tested fuel blend cetane number were higher than the EN590 minimum limit.…”
Section: Resultscontrasting
confidence: 95%
“…However, ethanol is easily attainable and contributes to emission reductions. Butyl levulinate is a promising oxygenated fuel candidate that has gained abundant of attention lately [19][20][21]. Its high oxygen content promotes reduced emissions.…”
Section: Selection Of Fuel Blend Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, ethyl levulinate, obtained by esterification of levulinic acid, is a versatile chemical compound and has been widely applied in food industry, as solvents and plasticizers. Besides, it can be used as an additive for transportation fuels, which shows excellent performance [11,12]. It is reported that furfuryl alcohol also can be converted into ethyl levulinate in the presence of an acid catalyst [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, BL has an evidently lower solubility in water (1.3 wt %) than EL (15.6 wt %). In diesel blends containing 20% (v/v) alkyl levulinate, EL was found to form a separate liquid phase from diesel at 283 K, while BL remained constant miscibility in diesel even at the diesel cloud point (247 K) [20].…”
Section: Introductionmentioning
confidence: 96%